2012
DOI: 10.1080/02705060.2012.662470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of riparian habitat on aquatic macroinvertebrate community colonization within riparian zones of agricultural headwater streams

Abstract: Little is known about aquatic macroinvertebrate colonization of aquatic habitats within riparian zones of headwater streams in the midwestern United States. Many headwater streams and their riparian habitats in this region have been modified for agricultural drainage. Riparian habitat modifications caused by agricultural drainage may influence aquatic macroinvertebrate colonization within the riparian zones of headwater streams. However, the effects of agricultural drainage-induced riparian modifications have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…These results are consistent with others [4,8,[37][38][39][40] who documented how changes in riparian structure alters Our results are also consistent with others [13,[41][42][43] who have documented decreased water temperatures within containers or aquatic habitats within forested riparian habitats having greater canopy cover than those within herbaceous riparian habitats. Williams et al [41] documented that containers placed in forested habitats had reduced water temperatures compared to containers placed in open fields in Canada.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with others [4,8,[37][38][39][40] who documented how changes in riparian structure alters Our results are also consistent with others [13,[41][42][43] who have documented decreased water temperatures within containers or aquatic habitats within forested riparian habitats having greater canopy cover than those within herbaceous riparian habitats. Williams et al [41] documented that containers placed in forested habitats had reduced water temperatures compared to containers placed in open fields in Canada.…”
Section: Discussionsupporting
confidence: 93%
“…Mokany et al [43] also found that increasing the amount of the shade found over temporary pools in Australia reduced water temperature within the pools. Despite an inability to account for the effect of time of day on water temperature measurements, Seger et al [13] periodically observed that water temperatures in water filled containers within forested riparian habitats having greater canopy cover were less than water temperatures in containers within herbaceous riparian habitats with less canopy cover adjacent to agricultural headwater streams in central Ohio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, higher invertebrate richness and abundance are commonly observed in forested rather than non-forested areas, and these areas also differ in species composition (Blaustein et al 1999, Ngai et al 2008, Seger et al 2012). These differences can be attributed mainly to the greater input of detritus in containers in the closed area (Kling et al 2007, Yee andJuliano 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, closed areas provide higher availability of food and habitats for different species, which can stimulate oviposition (Reiskind and Wilson 2004). Moreover, other factors may influence the community of Ceratopogonidae, such as predation or abiotic variables (Seger et al 2012, Rubio et al 2013.…”
Section: Discussionmentioning
confidence: 99%